ANALISIS KINERJA PEGAWAI KANTOR KECAMATAN PASANGKAYU KABUPATEN MAMUJU UTARA - Natili, Sefly Mey (Katalogis, 2018)
This study aimed to analyze employee performance based on duties and functions, and to analyze factors inhibiting employee performance based on duties and functions, at Pasangkayu District Office Mamuju Utara Regency. The concept used in this study to examine determinants of employee performance based on duties and functions was the Theory of Agus Dwiyanto, comprising Productivity, Quality, Service, Responsiveness, Responsibility, and Accountability. This study used purposive sampling with specified informants as much as 5 people and key informant was Head of Pasangkayu District, Mamuju Utara Regency. The data collection technique was observation, interview, and documentation. The results showed that employee performance at Pasangkayu District Office North Mamuju Regency had not been good seen from the aspect of accountability, many programs and services not running, and based on working procedures or method specified, resulting in unsatisfactory or such weak work results, and ultimately the effectiveness and efficiency was not achieved. The aspect of Service Quality was still low due to low personnel resources. The Accountability aspect at Pasangkayu District Office wherein employee adherence and responsibility to the rules had not been met resulting in unoptimal employee performance.